Distributed Finite‐Time Extended Dissipative Filtering and Event‐Triggered Strategy for Nonlinear Systems Over Sensor Networks With Two‐Channel Stochastic Attacks - Zhou, Xin; Chen, Guici; Zhu, Song; Chang, Xiao‐Heng; Shen, Mouquan (International journal of robust and nonlinear control, 2025)
ABSTRACT This study delves into the distributed finite‐time extended dissipative filtering problem and event‐triggered strategy for nonlinear systems over sensor networks with two‐channel stochastic deception attacks. A new distributed filter is proposed, which simultaneously addresses the event‐triggered strategy and two‐channel attack scenario. Here, the event‐triggered strategy is devised in a distributed manner, and the deception attack model following the Bernoulli distribution is established. Additionally, the finite‐time extended dissipative index is considered to resolve the finite‐time distributed H∞$$ H_{∞ } $$, L2−L∞$$ L_2-L_{∞ } $$, passive, and dissipative filtering problem within a unified framework. Sufficient conditions are derived to ensure stochastically finite‐time extended dissipation for filtering error systems through stochastic analysis and iterative methods. Finally, the numerical simulation example is provided to validate the theoretical results.